Impacts of regional energy markets on decentralised energy supply - Jens Maiwald (The Central European Review of Economics and Management (CEREM), 2018)
Aim: This paper aims to describe an approach to develop a simulation model for investigating regional energy markets. Therefore the so called Cellular Approach is combined with the approach of Agent-Based Modelling.Design / Research methods: The model is built as a bottom-up approach for integral load management. Thus, supply factors such as limitations in generation are integrated directly and display flexibility. Thereby each market participant has its own economic interest. By the use of specific behaviour patterns and learning effects each agent in the model can act individually. This enables the market model to simulate how actors behave in changing situations.~Conclusions / findings: The model shown in this paper provides an alternative to considerations of energy supply systems via equation-based optimization models. The combination of these two approaches enhances to observe two central aspects of the German energy turnaround, decentralisation and the consumers changing role at the energy market.~Originality / value of the article: The Cellular Approach offers potential benefits for integrating renewable energy sources in regional power supply. Often discussed on a technical level, this paper focuses on the economical side of this topic. Moreover, differing to other research activities usually using optimization techniques, an Agent-Based Model is formulated to simulate a regional energy market. In the combination of a supply system primarily based on renewable energy sources and enhanced with different types of energy storage it is possible to simulate a supply system of the future.
Keywords: 330; Energy Markets; Renewable Energy Sources; Agent-based Modelling; Cellular Approach; Energy